High Climate Sensitivity in the Community Earth System Model Version 2 (CESM2). Issue 14 (22nd July 2019) - Gettelman, A.; Hannay, C.; Bacmeister, J. T.; Neale, R. B.; Pendergrass, A. G.; Danabasoglu, G.; Lamarque, J.‐F.; Fasullo, J. T.; Bailey, D. A.; Lawrence, D. M.; Mills, M. J.
Abstract: The Community Earth System Model Version 2 (CESM2) has an equilibrium climate sensitivity (ECS) of 5.3 K. ECS is an emergent property of both climate feedbacks and aerosol forcing. The increase in ECS over the previous version (CESM1) is the result of cloud feedbacks. Interim versions of CESM2 had a land model that damped ECS. Part of the ECS change results from evolving the model configuration to reproduce the long‐term trend of global and regional surface temperature over the twentieth century in response to climate forcings. Changes made to reduce sensitivity to aerosols also impacted cloud feedbacks, which significantly influence ECS. CESM2 simulations compare very well to observations of present climate. It is critical to understand whether the high ECS, outside the best estimate range of 1.5–4.5 K, is plausible. Key Points: The Community Earth System Model Version 2 (CESM2) has an Equilibrium Climate Sensitivity (ECS) of 5.3 K ECS change is mostly due to atmospheric cloud feedbacks, with land surface impacts in intermediate versions Processes that impact ECS through cloud feedbacks also impact aerosol forcing of climate